Mapping Potential Zones for Ecotourism Ecosystem Services as a Tool to Promote Landscape Resilience and Development in a Brazilian Municipality - Roque Guerrero, Joao Vitor; Teixeira Gomes, Antonio Alberto; Lollo, Jose Augusto de [UNESP]; Moschini, Luiz Eduardo (Mdpi, 2020)
In recent decades, with the increasing global need for sustainable development, ecotourism has emerged as one of the most efficient activities that can be used to reconcile economic development with environmental conservation. A growing interest in the ecotourism and ecosystem services provided by landscapes makes such services increasingly necessary within municipal planning processes. This study aims to construct a geoenvironmental model based on geographic information systems (GISs) to spatially identify areas with greater capacity to promote ecotourism, with a practical case study of the city of Brotas, Brazil. The model can produce an integrated analysis of landscape components using geoenvironmental, topographic, and urban data. As a result, four zones were classified according to their ecotourism potential, with 81% of the overall local territory showing great potential, which not only reinforces the territory's resilience regarding sustainable development, but also demonstrates that ecotourism should be included in discussions related to environmental planning in Brotas, as well as in other municipalities that have ecotourism potential.
Keywords: landscape planning; GIS; ecotourism; ecosystem services; AHP; fuzzy inference; zoning